Associations of genome-wide and regional autozygosity with 96 complex traits in old order Amish - Lynch, Megan T.; Maloney, Kristin A.; Xu, Huichun; Perry, James A.; Center, Regeneron Genetics; Shuldiner, Alan R.; Mitchell, Braxton D. (BMC genomics, 2023)
Background: Autozygosity, the proportion of the genome that is homozygous by descent, has been associated with variation in multiple health-related traits impacting evolutionary fitness. Autozygosity (FROH) is typically measured from runs of homozygosity (ROHs) that arise when identical-by-descent (IBD) haplotypes are inherited from each parent. Population isolates with a small set of common founders have elevated autozygosity relative to outbred populations. Methods: In this study, we examined whether degree of autozygosity was associated with variation in 96 cardiometabolic traits among 7221 Old Order Amish individuals residing in Lancaster County, PA. We estimated the average length of an ROH segment to be 6350 KB, with each individual having on average 17.2 segments 1.5 KB or larger. Measurements of genome-wide and regional FROH were used as the primary predictors of trait variation in association analysis. Results: In genome-wide FROH analysis, we did not identify any associations that withstood Bonferroni-correction (p = 0.0005). However, on regional FROH analysis, we identified associations exceeding genome-wide thresholds for two traits: serum bilirubin levels, which were significantly associated with a region on chromosome 2 localized to a region surrounding UGT1A10 (p = 1 × 10− 43), and HbA1c levels, which were significantly associated with a region on chromosome 8 localized near CHRNB3 (p = 8 × 10− 10). Conclusions: These analyses highlight the potential value of autozygosity mapping in founder populations.